Sugarcane and Coffee in the Extreme Southern Region of Bahia, Brazil: A Spatio-Temporal Analysis and Socioeconomic Factors - Almeida, Regiane Oliveira; Cruz , Thyane Viana; Crepaldi , Maria Otávia; Silva , Leonardo Thompson; Sousa, Ana Cristina; Cerqueira, Everton Mateus Santos; Sena, Anderson (Sociedade & Natureza, 2023)
The extreme southern region of Bahia (ESRB - Extreme Southern Region of Bahia) has agricultural aptitude for several crops and has already been subjected to the expansion of sugarcane and coffee. Thus, this work analyzes the spatial and temporal dynamics of sugarcane and coffee monocultures in the ESRB and their relationship with socioeconomic indices. The methodology consists of collection and analysis of data from the Instituto Brasileiro de Geografia e Estatística (IBGE), which is the main provider of geographic information and statistics in Brazil, the Companhia Nacional de Abastecimento (CONAB), which is responsible for providing technical information to support your decision-making regarding the elaboration of policies aimed at agriculture and the Atlas Brasil platform. Data were collected regarding the planted area and the amount of sugarcane and coffee produced in the region between 1988 and 2019. To understand the relationship between expansion and socioeconomic factors, data related to gross domestic product (GDP) and municipal human development index (MHDI) were collected. This study identified the main sugarcane-producing municipalities (Caravelas, Mucuri, Medeiros Neto, Nova Viçosa, Lajedão, Ibirapuã and Santa Cruz Cabrália) and coffee (Prado, Itamaraju, Porto Seguro, Eunapolis, Teixeira de Freitas and Itabela). The expansion of these crops presents economic importance for the region, but presents a little contribution to the improvement of the various factors that make up the MHDI of the municipalities. This study concluded that the expansion of these crops changed the agricultural matrix of the region due to its specialization in the production of these crops to the detriment of others such as cocoa, for example.